PENGARUH KECUKUPAN MODAL DAN EFISIENSI OPERASIONAL TERHADAP KINERJA KEUANGAN PADA PT BANK KALBAR (PERSERO) TBK PERIODE 2014-2024 - Wel Wel; Ria Rosalia Simangunsong (CV. KAMPUS AKADEMIK PUBLISHING, 2026)
This study aims to analyze the effect of Capital Adequacy and Operational Efficiency on Financial Performance, proxied by Return on Assets (ROA), at PT Bank Kalbar (Persero) Tbk during the period 2014–2024. Capital adequacy is measured by the Capital Adequacy Ratio (CAR), while operational efficiency is measured by the Operating Expenses to Operating Income ratio (BOPO). The research employs a quantitative approach with descriptive and verificative research methods. The data used are secondary data obtained from the annual financial statements of PT Bank Kalbar (Persero) Tbk for the period 2014–2024. Data analysis techniques include descriptive statistics, classical assumption tests, multiple linear regression analysis, partial test (t-test), simultaneous test (F-test), and coefficient of determination (R²) using SPSS software. The results indicate that based on the partial test (t-test), Capital Adequacy Ratio (CAR) has an absolute t-value of 1.762, which is lower than the t-table value of 2.306, with a significance level of 0.116 > 0.05, indicating that CAR has no significant effect on financial performance (ROA). The Operational Efficiency (BOPO) variable also shows an absolute t-value of 0.731 < 2.306 with a significance level of 0.485 > 0.05, indicating that BOPO has no significant effect on ROA. Furthermore, the simultaneous test (F-test) shows an F-value of 2.902 < 4.46 with a significance level of 0.113 > 0.05, indicating that CAR and BOPO simultaneously have no significant effect on financial performance (ROA) at PT Bank Kalbar (Persero) Tbk during the period 2014–2024.